Clinical experience with ceftolozane/tazobactam in patients with serious infections due to resistant Pseudomonas aeruginosa. (June 2018) - Xipell, Marc; Paredes, Sandra; Fresco, Leticia; Bodro, Marta; Marco, Francesc; Martínez, J.A.; Soriano, Alex
Highlights: Ceftolozane/tazobactam (C/T) shows promising results against Pseudomonas aeruginosa infections. Prospective studies are needed to support its use in off-label indications. Better results for respiratory infections were observed with 2/1 g of C/T every 8 h compared with lower doses. Abstract: Objectives: The incidence of infections caused by multidrug-resistant Pseudomonas aeruginosa (MDR-Pa) has become a concern of increasing relevance nowadays. Ceftolozane/tazobactam (C/T) is a novel fifth-generation cephalosporin/β-lactamase inhibitor combination with activity against MDR-Pa. Methods: The clinical records of all patients diagnosed from May 2016 to May 2017 with an infection due to a MDR-Pa treated with C/T were retrospectively reviewed. Results: A total of 23 patients with 24 episodes of infection due to MDR-Pa were included. The minimum inhibitory concentration (MIC) of C/T against MDR-Pa ranged from 0.75–8 μg/mL. In 14 cases (58%) the use of C/T was off-label, including 8 respiratory tract infections (RTIs) and 6 skin and soft-tissue infections, whilst in 10 cases the use was for approved indications, including 7 urinary tract infections and 3 intra-abdominal infections. C/T was the first-line therapy in only three cases with a mean ± standard deviation treatment duration of 9.3 ± 4 days, and it was associated with another active drug (aminoglycoside or colistin) in 16 cases. The global clinical cure rate was 88% (21/24 episodes), and the 6-week mortality rate was 22% (5/23 patients) being higher in RTIs (37%). In these infections, three patients received 2/1 g every 8 h (q8h) and were cured without mortality, whilst three (60%) of five patients receiving 1/0.5 g q8h died. Conclusion: C/T had good clinical responses in different types of infection, including both FDA-accepted and off-label indications. The results support the use of higher doses in RTIs.